Sistem Integrasi (ISO 50001) Dengan Kombinasi Chi-Square Test Untuk Analisis Manajemen Penggunaan Energi Operasional Alat Berat Pada Perusahaan Terminal Pelabuhan - Ramadhana, Ridho Rizky; Prayitno, Yosephus Ardean Kurnianto; Irfan Bahiuddin; Setyawan Bekti Wibowo; Sugiyanto (Jurnal Teknologi dan Rekayasa Alat Berat, 2025)
Port terminal companies play an important role in the growth of international trade, with more than 85% of global cargo traffic transported via sea routes and ports. As international trade continues to grow in line with the increasing use of energy, it is necessary to implement energy management strategies to maximize energy utilization. An analysis of the energy management maturity level of a port terminal company based on ISO 50001, combined with a Chi-square test, was carried out to evaluate the actual use of fuel oil (BBM) in equipment. The results showed a maturity level value of ≥ 4 and a significant value in the Chi-square test, indicating an ideal condition for energy management in industrial companies. On the other hand, there is a fluctuating trend in the actual fuel oil usage ratio. This indicates that the company needs to regularly evaluate the alignment between managerial policy-making and actual field data, enabling the company to promptly address any deficiencies occurring on site.